Water chemistry of Lagrangian samplings of Inland Elbe 2022 (MOSES Hydrological Extremes) - Norbert Kamjunke; Wolf von Tümpling; Andrea Hoff; Matthias Koschorreck (PANGAEA, 2023)
The MOSES campaign ELBE 2022 covered the Czech freshwater Elbe, the German freshwater part, the tidal Elbe river, and the German Bight. Thus, the complete gradient from source to sea was investigated for the first time. The sampling will be conducted in a Langrangian way according to flow velocity. In the German freshwater Elbe, physico-chemical and biological parameters will be measured along the Elbe using the research vessel ALBIS from Schmilka (km 4, German border) to Geestacht (km 585, close to Hamburg). A particular scientific focus was on (1) composition of dissolved organic matter measured by high-resolution mass specrometry, (2) investigation of zooplankton besides bacteria and algae, and (3) greenhouse gas measurements in water and air (the latter was investigated in more detail during an addition campaing in Tangermünde in August 2022).